PERAN MEDIA SOSIAL DALAM MEMBENTUK OPINI MAHASISWA UNIVERSITAS NEGERI MEDAN TENTANG ISU POLITIK DI INDONESIA - Seevaira Chyta Simanullang; Iwain Oktaviona Nababan; Devi Permata Br. Bangun; Florensia Silaban; Halking (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of information technology has transformed the communication patterns and political behavior of young generations, including students at Universitas Negeri Medan (UNIMED). Social media has become the primary source for obtaining, understanding, and disseminating political information, thereby significantly shaping students’ political opinions. This study aims to analyze the role of social media in shaping UNIMED students’ opinions on political issues in Indonesia, identify their perceptions of political issues circulating on social media, and examine the influence of social media on the construction of their political views. Using a descriptive qualitative approach, the research employed surveys, observations, in-depth interviews, and documentation involving 27 UNIMED student informants. Data were analyzed through data reduction, data display, and verification techniques. The findings reveal that social media plays a significant role as students’ main political information source, directing their attention through algorithmic exposure, and influencing opinion formation through digital public interactions. Social media also acts as a discursive space where students actively express political views, while simultaneously posing risks of information bias, polarization, and misinformation. Overall, social media affects the cognitive, affective, and conative aspects of students in understanding and responding to national political issues